Acupuncture as an adjunct therapy for enhancing endometrial receptivity in female infertility: a literature review - Zhang, Shike; He, Hui; Wang, Jingyuan; Ma, Li; Wei, Xiaoyu; Zhang, Mingxing; Guo, Yi (Frontiers in Physiology, 2025)
Infertility remains a global challenge, with female factors accounting for the majority of cases. Endometrial receptivity (ER), the ability of the endometrium to accept and support embryo implantation, is a critical determinant of successful conception. Traditional Chinese medicine, specifically acupuncture, has been widely adopted as an adjunct therapy for enhancing ER and improving reproductive outcomes in infertile women. This literature review explores the efficacy and underlying mechanisms of acupuncture in promoting ER by focusing on key areas, including improvements in endometrial morphology, increasing uterine blood flow, adjustment to hormone levels, regulation of molecular markers, modulating endometrial immune-inflammatory microenvironment, and probably activating the somatosensory-autonomic reflex pathway. Although promising, existing studies on acupuncture and ER often face limitations in sample size and methodological rigor, highlighting the need for larger, high-quality randomized controlled trials (RCT). Furthermore, the safety profile of acupuncture in infertility treatment is favorable, with few reported adverse effects. These findings suggest that acupuncture could be a viable complementary therapy for improving pregnancy outcomes in women with compromised ER, although further research is essential to establish definitive protocols and mechanisms.